1992
DOI: 10.1111/j.1439-0450.1992.tb01183.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Group B Streptococcal Serotypes and Cell Surface Hydrophobicity

Abstract: Cell surface hydrophobicities of streptococci of serological group B were determined by the adherence of the bacteria to hexadecane droplets. A significant adherence to hexadecane was observed with the group B streptococcal type reference strains Ib, V, Ic, Rand X, but not with those of serotype Ia, 11, 111 and IV. Cultivation of the bacteria in microcapsule-inducing media reduced the hexadecane adherence properties. The adherence to hexadecane was not related to fibrinogen binding properties of the cultures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Numerous studies have described the ability of clinical S. agalactiae isolates to interact with human fibrinogen (11,56,62,81). Recently, Schubert et al (57) identified in S. agalactiae a fibrinogen-binding protein, which was termed FbsA.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have described the ability of clinical S. agalactiae isolates to interact with human fibrinogen (11,56,62,81). Recently, Schubert et al (57) identified in S. agalactiae a fibrinogen-binding protein, which was termed FbsA.…”
Section: Discussionmentioning
confidence: 99%
“…26 Strain 7805 (serotype Ib) was kindly provided by G. S. Chhatwal (Department of Microbial Pathogenesis and Vaccine Research, German Research Center for Biotechnology [GBF], Braunschweig, Germany), and strain 1504 (serotype V) was obtained from the collection of the National Reference Center for Streptococci in Aachen, Germany. S agalactiae was cultivated at 37°C in Todd-Hewitt broth containing 1% yeast extract.…”
Section: Bacterial Strains and Culture Conditionsmentioning
confidence: 99%
“…GBS cultures (strain 6313, serotype III, see [13]), were exposed to fibrinogen tagged by Fluorescein isothiocyanate (FITC) for 2 h at 22 C in an end-over-end mixer, and then centrifuged/resuspended to get rid of unbound FITC-Fbg. The microscope image in Fig.…”
mentioning
confidence: 99%